PENGGUNAAN MODUL OPERASI HITUNG DI SD NEGERI 3 KANOMAN PANJATAN KULONPROGO PASCA COVID 19 - Febriana, Rina; Hidayati, Ika Septi; Putri, Prihastini Oktasari (Gemi: Jurnal Penelitian dan Pengabdian, 2024)
The use of teaching aids in learning is very important because it becomes the basis for students to better understand the concept of abstract thinking. Props are certain objects that are intentionally made, collected, and arranged that are used to help instill or present mathematical concepts. One of the things about integer operations is integer subtraction. Integer math material, especially integer subtraction, needs to be taught to elementary school students, as seen after this pandemic, elementary school students have difficulty reducing integers. So we from the P2M team want to make it easier for these elementary students to use integers by using the arithmetic operations module. the concept of arithmetic operations (addition and subtraction) improves the quality of learning in terms of the use of media so that mathematics material becomes more concrete, and the implementation of training develops innovative learning